Konten Analisis Kriteria Green Road pada Dokumen Kontrak Konstruksi Jalan Kota Payakumbuh - Rahmad Aulia Nahar; Yossyafra -; Bayu Martanto Adji (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2020)
Road construction has negative side effects on the environment, including reduced non-renewable natural resources, increased emissions, construction waste, reduced productive land and damaged ecosystems. To minimize this problem environmentally friendly efforts are needed in the implementation of road construction. One of the efforts made is to use the concept of greenroad. This concept can be applied at every stage of the implementation of road construction, especially at the stage of road construction and maintenance. This study aims to assess the application of greenroad criteria in construction contract documents using the Content Analysis method. While the case study examined is the Payakumbuh City Road Rehabilitation / Maintenance Contract document in 2016, 2017 and 2018 with a contract value above four billion rupiah. Greenroad assessment criteria use PUPR Minister Circular Number 04/SE/M/2018 concerning GreenRoad Ranking Guidelines. In this guide the assessment of greenroads is grouped into five categories, 35 subcategories and 84 criteria. The categories are Conservation of environment, water, air and nature (KL), Provision of transportation and community (TM), Construction implementation activities (AK), Use of materials and natural resources (MS), Pavement technology (TP). The criteria contained in each subcategory have a weighted value. The maximum total value possible in this scoring system is 100. While the greenroad ranking system is divided into four levels, represented by the number of stars. While the greenroad ratings for contracts in 2017 and 2018 are 2 stars with 15.01 each. The increase in value in 2017 is in the AK category with a value of 3.36 in 2016 to 5.46 in 2017. While the opportunity to add green road criteria to the Periodic Road Rehabilitation/ Maintenance contract can be applied in the GCC (general terms of the contract) and technical specifications as many as 26 criteria. Keywords: green road, adjusment criteria, content analisys, contract